Connectivity dependent thermopower of bridged biphenyl molecules in single-molecule junctions. Issue 27 (3rd July 2020) - Grace, Iain M.; Olsen, Gunnar; Hurtado-Gallego, Juan; Rincón-García, Laura; Rubio-Bollinger, Gabino; Bryce, Martin R.; Agraït, Nicolás; Lambert, Colin J.
Abstract : We report measurements on gold|single-molecule|gold junctions, using a modified scanning tunneling microscope-break junction (STM-BJ) technique, of the Seebeck coefficient and electrical conductance of a series of bridged biphenyl molecules. Abstract : We report measurements on gold|single-molecule|gold junctions, using a modified scanning tunneling microscope-break junction (STM-BJ) technique, of the Seebeck coefficient and electrical conductance of a series of bridged biphenyl molecules, with meta connectivities to pyridyl anchor groups. These data are compared with a previously reported study of para -connected analogues. In agreement with a tight binding model, the electrical conductance of the meta series is relatively low and is sensitive to the nature of the bridging groups, whereas in the para case the conductance is higher and relatively insensitive to the presence of the bridging groups. This difference in sensitivity arises from the presence of destructive quantum interference in the π system of the unbridged aromatic core, which is alleviated to different degrees by the presence of bridging groups. More precisely, the Seebeck coefficient of meta -connected molecules was found to vary between −6.1 μV K −1 and −14.1 μV K −1, whereas that of the para -connected molecules varied from −5.5 μV K −1 and −9.0 μV K −1 .